Analysis of the Basic Characteristics of the Working Accuracy of the Atomic Diffusion Additive Manufacturing ADAM Process by Comparison with the Selective Laser Melting SLM Process - Czan, Andrej; Czanova, Tatiana; Holubjak, Jozef; Novak, Martin; Czanova, Natalia; Czan, Andrej; Krisak, Dominik (Manufacturing Technology Journal, 2024)
Atomic Diffusion Additive Manufacturing (ADAM) is a progressive layering process based on metallic materials with a plastic binder designed to extruse the material. The ADAM process can be classified as an indirect additive manufacturing process in which a solid fiber of metal powder enclosed in a plastic binder is applied. After creating a 3D object by the ADAM process, the excess plastic binder is removed in the cleaning chamber and vacuum sintering of the 3D object is performed. This work aims to provide a preliminary characterization of the ADAM process and compare the achieved results with the application most implemented so far in additive manufacturing for metal 3D objects using Selec-tive Laser Melting SLM. In particular, the density and microstructure of the applied process and mate-rial 17-4PH are studied, while optimal or recommended technological parameters of production facili-ties are applied. Furthermore, the dimensional accuracy of the ADAM process is observed, which is evaluated by means of IT accuracy levels according to the ISO reference artifact. Due to the applied AM process, the final character of a 3D object depends on technological parameters. The weight of a 3D object is low compared to the material processed by additive manufacturing processes in a powder bed. The dimensional accuracy and roughness of the surface depends on the geometry, orientation, and position of the individual shape specifications of the 3D object. Additive technologies generally achieve a degree of accuracy of approximately IT12 to IT13, which is comparable to traditional semi-finished metal manufacturing processes.
Keywords: Additive Manufacturing; Metal 3D Objects; Dimensional Accuracy; Shape Accuracy; Surface Roughness